The impact of environmental tax reform on industrial green development: evidence from China - Lu, Zhaoyang; Gou, Diao; Yang, Lanqin; Wu, Ziyue; Feng, Hailong (Frontiers in Environmental Science, 2025)
IntroductionThe transformation of environmental protection fees into environmental protection taxes in China reflects a broader commitment to ecological civilization. This reform aligns fiscal instruments with environmental objectives, aiming to internalize environmental costs and incentivize greener industrial behavior. However, empirical evidence on its actual impact on industrial green development remains limited. This study addresses this gap by investigating how the reform affects green total factor productivity (GTFP) in key industrial sectors.MethodsWe build a Difference-in-Differences model to assess the causal impact of the 2018 environmental tax change, using it as a quasi-natural experiment. A-share listed companies in industries with high levels of pollution from 2013 to 2022 are included in the sample. To further explore the transmission mechanism, we use mediation effect models to test whether the reform influences GTFP through changes in the degree of resource misallocation and green technological innovation. Multiple robustness checks, including parallel trends test, propensity score matching and placebo test, are conducted to ensure result validity.ResultsThe results indicate that the reform significantly improves industrial green development, as measured by firm-level GTFP. In state-owned and highly polluting businesses, the effect is particularly noticeable. According to mechanism testing, the policy effect is communicated through a decrease in the degree of resource misallocation and more investment in green innovation. These findings are robust across alternative model specifications and variable definitions.DiscussionThis study offers new insights into how environmental tax policies contribute to sustainable industrial transformation. It highlights the importance of fiscal policy tools in steering firm behavior toward greener practices. Policymakers should focus on refining tax enforcement and complementing it with innovation incentives to amplify the reform’s effectiveness. The evidence underscores the critical role of institutional design in aligning industrial growth with environmental goals.